Lessons from community engagement to improve COVID-19 diagnosis and treatment in Cochabamba, Bolivia - Elizabeth Posada; Nilce Mendoza; Cristina Alonso-Vega; Claire Billot; Beatriz Mallén Muñoz; Leonardo de la Torre; Adalid Paiva; Luis Villarroel; Regina Rabinovich (Taylor & Francis Group, 2024)
Background Community engagement is recognized as a vital component of health-related research and programs, particularly during infectious disease outbreaks and epidemics. Despite the importance of engaging communities in the response to COVID-19, relatively little research has examined how this was (or was not) achieved, and even less in low- and middle-income countries. This article describes the community engagement that accompanied efforts to strengthen COVID-19 diagnosis and treatment as part of the ECO Project in Cochabamba, Bolivia and highlights lessons for future pandemic response. Methods Community engagement involved formative assessment, co-creation to develop a health information campaign, ongoing community listening and evaluation. Qualitative data were collected during workshops, project meetings and focus groups. Questionnaire-based surveys were conducted to assess COVID-19-related attitudes, knowledge and practices. Results The collected data highlighted the value of working closely with well-established community health committees and involving community members with social media skills in the design of COVID-19-related messages to address on- and offline misinformation. Co-creation sessions enabled the adjustment of the information campaign in terms of content and approach based on the needs and preferences of community members and health staff. The continuous listening with community and health personnel facilitated the ongoing adaptation of project activities. Conclusion Through a stepped and multi-pronged approach, incorporating co-creation and community listening, the engagement could respond to emerging local challenges during the pandemic. The project created spaces for dialogue and opportunities for collaboration that strengthened links between the community and the health services.